Modified security model based on dynamic trusted degree - NIE Xiao-wei1; FENG Deng-guo1 (Tongxin xuebao)
A modified security model based on dynamic trusted degree security model MSMBDTD（modified security model based on dynamic trusted degree） was proposed.Based on the trusted authentication and measurement of trusted computing,MSMBDTD first gave definition of trusted degree rule.Then it analyzed dynamic transformation of trusted degree in the course of system running.And also it modified access privilege of subject,which made access range be in conformance with trusted degree.Finally,after formal description and safety analysis with proof are given,MSMBDTD can support access control based on trusted degree.